Outcomes of Video-Assisted Thoracoscopic Surgery for Lung Cancer Performed by a Team of General Surgeons - A Retrospective Study. Issue 2 (2019) - Fukai, Ryuta; Nishida, Tomoki; Kume, Nao; Murata, Takaaki; Miyake, Katsunori; Isogai, Naoko; Shimoyama, Rai; Kawachi, Jun; Kurata, Shyuji; Iijima, Hidekazu; Watanabe, Kazunao
No abstract available